PROBLEMATICS OF „IMPERIAL DISCOURSE“ IN THE MODERN STUDIES OF RUSSIAN CULTURE - Snežko, Julija (Politologija, 2015)
This article aims at discussing general problems concerning the relationship between empire and culture/literature and possible ways of its investigation. On the basis of the works of Michel Foucault, Edward W. Said, Aleksandr Etkind, Ewa M. Thompson, Susan Layton, Richard S. Wortman, Andrej Zorin and Harsha Ram it can be concluded that the relationship between empire (or imperial context) and literature can be conceptualized with the help of the notion of imperial discourse. This notion covers corresponding texts, specific poetics and imperial practices manifested through different power relations. Theoretical investigations of discourse by Foucault introducing the idea of close connection between power, knowledge and text became a great impetus to thurther studies of relationship between culture/literature and imperial context.Thus these relations in the case of British Empire were conceptualized as orientalism by Said. Later Said’s ideas were applied to investigation of Russian culture by Thompson, who focused exlusively on negative side of Russian orientalism and imperialism and what, consequently, made her work too ideologized. Etkind, in turn, elaborated and applied the idea of inner colonization to Russian culture, showing how russian “narod” was treated as “Other” in some famous russian novels. Layton, on the other hand, applied Said’s implications to thematization of Caucasus in Russian literature, demonstrating a quite ambiguous relationship of russian writers to imperial project and role of Caucasus in construction of their national identity.Wortman and Zorin turn themselves to investigation of the symbolics of imperial power: in the works of Wortman imperial discourse is studied as the developing set of imperial myths, values and court ceremonies, while Zorin performs a survey of ideological side of literature marking special role of ideological symbols and metaphors in the formation of imperial ideology. And, lastly, Ram performs his analysis on the level of text poetics demonstrating the connection of poetics with historical dimension.All these investigations touch different aspects of text functioning in defined socio-historical (imperial) context and show, how imperial discourse can be studied on different levels ranging from investigation of various courtly ceremonies, imperial practises and mythology, inquiring into literary representations and textual means (use of metaphors, themes, and etc.) to specific generic poetics.